2018
DOI: 10.1017/s0305000918000478
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual phonological acquisition: the influence of language-internal, language-external, and lexical factors

Abstract: This study examines the influence of language-internal (frequency and complexity of linguistic properties), language-external (percent French input, socioeconomic status (SES), and gender), and lexical factors (size of total and French vocabulary) on the phonological production abilities of monolingual and bilingual French-speaking children, aged 2;6. Children participated in an object and picture naming task in which they produced words selected to test different phonological properties. The bilinguals’ first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(70 citation statements)
references
References 75 publications
8
55
2
5
Order By: Relevance
“…When examining the differences between types of bilinguals, a distinction can be made between simultaneous bilinguals (those who learned two languages at the same time) and sequential bilinguals (those who learned one language followed by another). Kehoe and Havy (2019) show that language dominance has less of an effect on phonetic transfer in early sequential and simultaneous bilinguals than in late sequential bilinguals. While some studies have suggested that early sequential and simultaneous bilinguals do not differ drastically from monolinguals of both languages (Guion 2003;Mack 1989), Fowler et al (2008 suggests that there are differences in production between these groups.…”
Section: Almediina Aljamilamentioning
confidence: 73%
See 3 more Smart Citations
“…When examining the differences between types of bilinguals, a distinction can be made between simultaneous bilinguals (those who learned two languages at the same time) and sequential bilinguals (those who learned one language followed by another). Kehoe and Havy (2019) show that language dominance has less of an effect on phonetic transfer in early sequential and simultaneous bilinguals than in late sequential bilinguals. While some studies have suggested that early sequential and simultaneous bilinguals do not differ drastically from monolinguals of both languages (Guion 2003;Mack 1989), Fowler et al (2008 suggests that there are differences in production between these groups.…”
Section: Almediina Aljamilamentioning
confidence: 73%
“…Languages 2019, 4, x FOR PEER REVIEW word boundaries. Spanish and Arabic have different p they each utilize different strategies for resyllabificatio L1 Arabic to L2 Spanish in Arabic-Spanish bilinguals, l study aims to investigate whether Arabic-Spanish bil boundaries differently than Spanish monolinguals du findings of previous research (e.g., Biondi Assali 1989bHavy 2019Van Coetsem 1988;Winford 2003), we ex sequential) and language dominance have an effect on of the two vowels and stress of the second vowel affect (Barbería 2012;Hualde 2014;Hualde and Prieto 2002). T strategies acoustically as a result of transfer in Arabic-S these languages in contact in the Caribbean in general.…”
Section: ˈ Amentioning
confidence: 99%
See 2 more Smart Citations
“…Studies examining the influence of language-internal, language-external, and lexical factors on phonological production Kehoe and Havy (2019) investigated the influence of language-internal, languageexternal, and lexical factors on the phonological production skills of monolingual and bilingual French-speaking two-and-a-half-year-olds. The bilinguals had differing first languages (L1s) (e.g., Spanish, Portuguese, English, etc.)…”
Section: Bilingual Statusmentioning
confidence: 99%